2010
DOI: 10.1124/dmd.110.035907
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Disposition of the Sphingosine 1-Phosphate Receptor Modulator Fingolimod (FTY720) in Healthy Volunteers: A Case of Xenobiotic Biotransformation Following Endogenous Metabolic Pathways

Abstract: ABSTRACT:Fingolimod [(FTY720), Gilenya; 2-amino-2-[2-(4-octylphenyl)ethyl]-1,3-propanediol], a new drug for the treatment of relapsing multiple sclerosis, acts through its phosphate metabolite, which modulates sphingosine 1-phosphate receptors. This represents a novel mechanism of action. In the present work, the absorption and disposition of 14 C-labeled fingolimod were investigated in healthy male volunteers after a single oral dose of 4.5 mg. Total radioactivity was determined in blood, urine, and feces. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
36
1
Order By: Relevance
“…The important role of the liver in the metabolism of fingolimod was shown in liver impaired patients: fingolimod AUC increased and its half-life was prolonged and exposure to fingolimod phosphate increased in a manner related to the severity of the liver function impairment [62]. Absorption and disposition of 14 C-labeled fingolimod were further investigated in healthy subjects [64] and revealed that fingolimod is mainly metabolized via three pathways and the major route of excretion is urine. Administration of fingolimod intravenously and orally allowed to estimate a high apparent absolute bioavailability of 93 % [65].…”
Section: Pharmacokinetics Of Fingolimodmentioning
confidence: 99%
“…The important role of the liver in the metabolism of fingolimod was shown in liver impaired patients: fingolimod AUC increased and its half-life was prolonged and exposure to fingolimod phosphate increased in a manner related to the severity of the liver function impairment [62]. Absorption and disposition of 14 C-labeled fingolimod were further investigated in healthy subjects [64] and revealed that fingolimod is mainly metabolized via three pathways and the major route of excretion is urine. Administration of fingolimod intravenously and orally allowed to estimate a high apparent absolute bioavailability of 93 % [65].…”
Section: Pharmacokinetics Of Fingolimodmentioning
confidence: 99%
“…In terms of metabolites, hydroxylation of both FTY720-C2 and FTY720-Mitoxy were identified early in 1 hr incubations (Figs 1 and 3). As previously mentioned in the Introduction to this paper, one of the biotransformation pathways of FTY720 is ω-hydroxylation at the octyl chain being the first step, followed by further oxidation and subsequent β-oxidation to yield different length carboxylic acid metabolites [41]. Human hepatocytes generated similar levels of hydroxy FTY720-C2 and FTY720-Mitoxy (Figs 1B and 3B), but in rat hepatocytes, hydroxy FTY720-C2 was produced in larger amounts than was hydroxy FTY720-Mitoxy (Figs 1A and 3A); again, suggesting species-specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…The full absorption, distribution, metabolism, and excretion (ADME) data on FTY720 (fingolimod) are well described for humans [3941]. FTY720 blood concentrations slowly reach maxima at ~ 12 to 24 hr after oral dosing and follow a slow decline with elimination half-life of about 7 days [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Fingolimod-P is dephosphorylated back to fingolimod before it is eliminated from the body (Zollinger et al, 2011). 3.…”
Section: Methodsmentioning
confidence: 99%